Success, Failure, and Entrepreneurial Reentry: An Experimental Assessment of the Veracity of Self‐Efficacy and Prospect Theory. (16th April 2015) - Hsu, Dan K.; Wiklund, Johan; Cotton, Richard D.
Abstract : This paper develops and tests a model of an individual's intention to reenter entrepreneurship following business exit. Two long‐standing theories, prospect theory and self‐efficacy, seem to develop opposite predictions in this context. To reconcile these conflicting predictions, we theorize a moderating model and test the boundary conditions of both theories. Relying on two experimental studies, we find that prospect theory explains reentry intentions of entrepreneurs who have lost money when their self‐efficacy is moderate or low. Thereby, we provide an explanation for the puzzling empirical finding that so many failed entrepreneurs reenter entrepreneurship even if failure has undermined their self‐efficacy.